Refractory high-entropy alloy particle reinforced aluminum-based composite material and layered scanning additive manufacturing method thereof
By using refractory high-entropy alloy particles as reinforced phases in aluminum-based composite materials and using layered scanning additive manufacturing methods, the problems of premature failure and poor interface wettability caused by ceramic reinforced particles are solved, and aluminum-based is realized Significant improvement in the mechanical properties of composite materials and improvement in the forming quality.
Patent Information
- Application Number
- CN202411462148.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-18
AI Technical Summary
In the additive manufacturing process, existing aluminum-based composite materials have premature failure due to the addition of ceramic reinforced particles, poor interface wettability between the reinforced phase and the aluminum matrix, and process parameters cause problems in the composite material to remain stress.
Refractory high-entropy alloy particles are used as the reinforced phase. Through layered scanning additive manufacturing method, laser scanning speed and process parameters are adjusted, laser absorption rate is improved, thermal gradient inside the melt pool is uniform, and forming quality is improved.
The mechanical properties of aluminum-based composite materials are significantly improved, including the improvement of yield strength and tensile strength, reducing the anisotropy of the composite materials, improving the forming quality and reducing internal stress residues.
Smart Images

Figure CN119387609A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing of metal-based composite materials, and specifically relates to an aluminum-based composite material reinforced with refractory high-entropy alloy particles and a layered scanning additive manufacturing method thereof. Background Art
[0002] With the rapid development of technology in the fields of aerospace, automobile, rail transportation, etc., higher requirements are placed on the strength and other properties of aluminum alloys. Aluminum-based composite materials use aluminum alloy as the matrix, and improve the performance of the matrix material by adding reinforcements. The commonly used reinforcement phase is mainly ceramic materials. Although the ceramic reinforcement phase has high strength and hardness, the interface between ceramic particles and aluminum matrix has poor wettability and low bonding strength, which can easily cause plastic deviation of the composite material, limiting the application of ceramic particle reinforced aluminum-based composite materials. Therefore, how to choose a more suitable reinforcement particle to further explore the mechanical performance potential of aluminum-based composite materials is an urgent problem to be solved in this field.
[0003] Refractory high entropy alloys are mainly composed of W, Ta, Mo, Nb, V, Ti, Hf and other elements. Such high entropy alloys have excellent characteristics such as high melting point and high strength. Studies have found that high entropy alloys and aluminum matrix have similar thermal expansion coefficients, and the natural interface bonding characteristics between metals make the interface wettability between high entropy alloys and aluminum matrix good, and some elements such as Ti, Ta, Nb and other elements can form Al3Ti and other grain refiners with aluminum matrix, thereby refining the grains of aluminum matrix. At present, there are reports on high entropy alloys as reinforcement phases, but they are mainly concentrated in traditional FeCoCrNi and AlCoCrFeNi high entropy alloys, and there are no reports on the preparation of aluminum-based composites using refractory high entropy alloys as reinforcement phases.
[0004] Additive manufacturing technology is one of the important preparation technologies for aluminum-based composite materials. Commonly used technologies include laser selective melting. Due to the high reflectivity of aluminum alloy to infrared laser, the presence of the reinforcement phase can effectively improve the absorption rate of the laser, and this technology can form parts with complex shapes. During the laser printing process, the unique thermal history and high temperature gradient inside the molten pool easily cause large thermal stress in the parts during solidification. It has been reported that the use of laser remelting technology to regulate the thermal history and temperature gradient inside the molten pool can reduce internal defects and residual stress and improve the quality of part forming, but it also greatly increases the time and cost of material preparation. At present, there has been no report on the use of layered scanning to improve the organization and performance of composite materials while ensuring printing efficiency. Therefore, the reasonable design of relevant process parameters is an urgent problem to be solved by technicians in the preparation of aluminum-based composite materials.
[0005] In summary, in order to further improve the performance of aluminum alloys and expand the application scope of aluminum alloys, the development of new aluminum-based composite materials systems and their preparation methods are of great significance to the fields of aerospace, automobiles, rail transportation, etc. Summary of the invention
[0006] In order to solve the above problems, the purpose of the present invention is to provide an aluminum-based composite material reinforced with refractory high-entropy alloy particles and a layered scanning additive manufacturing method thereof, so as to solve the problems in the prior art that the addition of ceramic reinforcing particles will cause premature failure of the aluminum-based composite material prepared by additive manufacturing, poor interface wettability between the reinforcement phase and the aluminum matrix, and residual internal stress of the composite material caused by process parameters.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A refractory high entropy alloy particle reinforced aluminum-based composite material and a layered scanning additive manufacturing method thereof, wherein the material composition is characterized in that the matrix is various aluminum alloys, including cast aluminum alloys, such as Al-Si series, Al-Cu series, Al-Mg series, Al-Zn series; and some deformed aluminum alloys, such as 1 series, 2 series, 4 series, 5 series, and 6 series aluminum alloys. The reinforcement phase is a refractory high entropy alloy, including TiNbZrTa series, WTaMoNb series, HfNbZrTa series, TiTaNbV series, TiNbHfZr series and other high entropy alloys.
[0009] Furthermore, the mass fraction of the refractory high entropy alloy powder is between 1 and 10%, the mass fraction of the aluminum alloy powder is between 90 and 99%, and the sum of the two is equal to 100%. The refractory high entropy alloy powder is spherical and has a particle size between 1 and 53 μm, and the aluminum alloy powder is spherical and has a particle size between 1 and 90 μm.
[0010] The layered scanning additive manufacturing method of the refractory high entropy alloy particle reinforced aluminum-based composite material of the present invention specifically comprises the following steps:
[0011] (1) Preparation of composite powder: Weigh a certain mass fraction ratio of refractory high entropy alloy powder and aluminum alloy powder respectively, mix them evenly through a powder mixing device, pass a protective gas, sieve through a standard sieve, and then dry to obtain a composite powder of refractory high entropy alloy particles reinforced with aluminum alloy.
[0012] (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling and slicing are performed using 3D software; the composite powder is spread flat on the substrate of the SLM (Selective Laser Melting, SLM) metal 3D printer forming chamber, the substrate is preheated in a protective gas atmosphere, the laser power, scanning spacing, etc. are adjusted, and the scanning speed is graded and controlled: every 5 layers is a cycle, the first layer scanning speed is A mm / s, the second layer scanning speed is A+n×100mm / s, the third layer scanning speed is A+2n×100mm / s, the fourth layer scanning speed is A+3n×100mm / s, the fifth layer scanning speed is A+4n×100mm / s, and the first layer scanning speed of the next cycle is still A mm / s, and so on, so that the laser periodically scans layer by layer on the powder bed to print the aluminum-based composite material. The schematic diagram of layered scanning additive manufacturing is shown in the figure. Figure 1 shown.
[0013] Preferably, the powder mixing equipment described in step (1) is a ball mill or a V-type powder mixer, wherein the ball milling time is 4 to 10 hours, the rotation speed is 120 to 200 rpm, the grinding balls are ZrO2 grinding balls or stainless steel grinding balls, the grinding ball size is 1 to 5 mm, the ball-to-material ratio is 1:1 to 5:1, and the protective gas is nitrogen or argon, etc.; the V-type powder mixer mixing time is 4 to 8 hours. After the powders are mixed evenly, they are sieved and dried in a vacuum environment at 70 to 100° C. for 3 to 6 hours.
[0014] Preferably, in step (2), the substrate used in the printing process is 1 series, 2 series, 4 series, 5 series, or 6 series aluminum alloy, and the substrate is preheated in a nitrogen or argon atmosphere at a temperature of 100°C to 200°C.
[0015] Preferably, in step (2), the laser power is 300-380W, the scanning interval is 100-160μm, and the powder layer thickness is 20-40μm. The hierarchical control of the scanning speed: wherein n=(1, 2, 3) and n is the same number throughout the printing process, the scanning speed A mm / s and A+4n×100mm / s are both in the range of 900-2100mm / s.
[0016] A refractory high entropy alloy particle reinforced aluminum-based composite material is prepared by the above laser selective melting process.
[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0018] The present invention discloses a method of adding a refractory high entropy alloy as a reinforcement phase to an aluminum-based composite material. On the one hand, the refractory high entropy alloy powder is dispersed and distributed inside the aluminum alloy powder, which can improve the laser absorption rate and improve the forming quality during the printing process; on the other hand, due to the large difference in melting point between the refractory high entropy alloy and the aluminum matrix, and the high entropy alloy and the aluminum matrix have a natural good wettability, most of the refractory high entropy alloy particles can be completely retained inside the matrix, and the interface has a good metallurgical bond. During the printing process, the scanning speed is adjusted in stages to achieve layered scanning, which can effectively homogenize the thermal gradient inside the molten pool and avoid defects such as cracks and holes during the forming process. And because there are some elements in the refractory high entropy alloy that refine the aluminum alloy grains, the growth mode of the aluminum alloy grains is changed, and the growth of columnar crystals is transformed into equiaxed crystal growth in parallel to the construction direction, which significantly improves the mechanical properties of the aluminum-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of layered scanning additive manufacturing.
[0020] Figure 2 This is a metallographic structure diagram of the composite material obtained by printing in Example 1 perpendicular to the building direction.
[0021] Figure 3 This is a metallographic structure diagram of the composite material obtained by printing in Example 1 parallel to the building direction.
[0022] Figure 4 The metallographic structure diagram of AlSi10Mg parallel to the building direction obtained by printing for comparative example.
[0023] Figure 5 The room temperature tensile curves of the composite materials obtained by printing in Example 1 and the comparative example. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings. The embodiments listed below are only some embodiments of the present invention, and it should be understood that the protection scope of the present invention is not limited thereto.
[0025] Example 1
[0026] Step (1) Preparation of composite powder: The selected refractory high entropy alloy powder is TiNbZrTa with a particle size of 1 to 25 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm; weigh a certain mass ratio of refractory high entropy alloy powder and aluminum alloy powder, wherein the mass fraction of TiNbZrTa powder is 2%, and the rest is AlSi10Mg powder, and mix them by ball milling. The sizes of the stainless steel grinding balls used are 1 mm, 3 mm, and 5 mm. Weigh stainless steel balls at a mass ratio of 15:5:3, and the ball-to-material ratio is 2:1. Add the powder and grinding balls into a ball mill and mix for 4 hours, fill with argon as a protective gas, and rotate at 100 rpm. After mixing, sieve through a sieve and dry in a vacuum drying oven at 70°C for 4 hours to obtain a composite powder of TiNbZrTa and AlSi10Mg.
[0027] Step (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling and slicing are performed using three-dimensional software. The composite powder in step (1) is spread flat on the substrate of the SLM metal 3D printer forming cabin. In this embodiment, a 5083 aluminum alloy plate is selected, which is preheated to 150°C. The protective atmosphere in the printing cabin is argon. The printing process parameters are set as follows: the laser power is 350W, the scanning interval is 150μm, the powder layer thickness is 30μm, and the scanning speed is graded and regulated: every 5 layers is a cycle, the scanning speed A of the first layer is 1000mm / s, in this embodiment n=2, and the scanning speeds of the next four layers are 1200mm / s, 1400mm / s, 1600mm / s, and 1800mm / s respectively. The aluminum-based composite material is printed in this cycle.
[0028] The prepared aluminum-based composite material was subjected to microstructure characterization, hardness testing and room temperature tensile mechanical property testing that met national standards. Figure 2 This is the metallographic structure of the composite material obtained by printing in Example 1 perpendicular to the construction direction. It can be seen that spherical refractory high entropy alloy particle reinforcement phases are distributed inside the aluminum matrix. Figure 3 The metallographic structure parallel to the build direction is shown. The refractory high entropy alloy particles are well bonded to the aluminum matrix interface. Compared with the metallographic structure of AlSi10Mg printed in the comparative example parallel to the build direction, it can be seen that the matrix structure is grown by columnar crystals ( Figure 4 ) transforms into equiaxed crystal growth ( Figure 3 ). By comparing the tensile properties of Example 1 with those of the comparative example, it was found that the yield strength and tensile strength of the aluminum-based composite material were greatly improved, from 208.55MPa and 382.07MPa to 311.73MPa and 483.55MPa, respectively, and the elongation was maintained at 4.67%. Figure 5 As shown, the hardness also increased from 126.4HV to 161.9HV.
[0029] Example 2
[0030] Step (1) Preparation of composite powder: The selected refractory high entropy alloy powder is TiNbZrTa with a particle size of 15 to 53 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm; weigh a certain mass ratio of refractory high entropy alloy powder and aluminum alloy powder, wherein the mass fraction of TiNbZrTa powder is 3%, and the rest is AlSi10Mg powder, and mix them by ball milling. The sizes of the stainless steel grinding balls used are 1 mm, 3 mm, and 5 mm. Weigh stainless steel balls at a mass ratio of 15:5:3, and the ball-to-material ratio is 1:1. Add the powder and grinding balls into a ball mill and mix for 6 hours, fill with argon as a protective gas, and rotate at 120 rpm. After mixing, sieve through a sieve and dry in a vacuum drying oven at 70°C for 4 hours to obtain a composite powder of TiNbZrTa and AlSi10Mg.
[0031] Step (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling and slicing are performed using three-dimensional software. The composite powder in step (1) is spread flat on the substrate of the SLM metal 3D printer forming cabin. In this embodiment, a 5083 aluminum alloy plate is selected, which is preheated to 150°C. The protective atmosphere in the printing cabin is argon. The printing process parameters are set as follows: the laser power is 350W, the scanning interval is 150μm, the powder layer thickness is 30μm, and the scanning speed is graded and regulated: every 5 layers is a cycle, the scanning speed A of the first layer is 1000mm / s, in this embodiment n=2, and the scanning speeds of the next four layers are 1200mm / s, 1400mm / s, 1600mm / s, and 1800mm / s respectively. The aluminum-based composite material is printed in this cycle.
[0032] The prepared aluminum-based composite material was subjected to microstructure characterization, hardness test, and room temperature tensile mechanical property test that meets national standards. It can be found that the yield strength and tensile strength of the aluminum-based composite material were greatly improved, increasing to 326.49MPa and 497.68MPa respectively, the elongation was maintained at 4.53%, and the hardness was also increased to 172.68HV. Figure 2 , 3 Similar) found that more spherical particles are distributed in the matrix and the interface bonding is good.
[0033] Example 3
[0034] Step (1) Preparation of composite powder: The selected refractory high entropy alloy powder is WTaMoNb with a particle size of 1 to 25 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm; weigh a certain mass ratio of refractory high entropy alloy powder and aluminum alloy powder, wherein the mass fraction of WTaMoNb powder is 1%, and the rest is AlSi10Mg powder, and mix them by ball milling. The sizes of the stainless steel grinding balls used are 1 mm, 3 mm, and 5 mm. Weigh stainless steel balls at a mass ratio of 15:5:3, and the ball-to-material ratio is 1:1. Add the powder and grinding balls into a ball mill and mix for 8 hours, fill with argon as a protective gas, and rotate at 140 rpm. After mixing, sieve through a sieve and dry in a vacuum drying oven at 70°C for 4 hours to obtain a composite powder of WTaMoNb and AlSi10Mg.
[0035] Step (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling and slicing are performed using three-dimensional software. The composite powder in step (1) is spread flat on the substrate of the SLM metal 3D printer forming cabin. In this embodiment, 5083 aluminum alloy plate is selected, preheated to 200°C, and the protective atmosphere in the printing cabin is argon. The printing process parameters are set as follows: laser power is 300W, scanning spacing is 140μm, powder layer thickness is 30μm, and the scanning speed is graded and regulated: every 5 layers is a cycle, the first layer scanning speed A is 900mm / s, in this embodiment n=3, and the scanning speeds of the next four layers are 1200mm / s, 1500mm / s, 1800mm / s, and 2100mm / s respectively. Printing of aluminum-based composite materials is carried out in this cycle.
[0036] The prepared aluminum-based composite material was subjected to microstructure characterization, hardness test, and room temperature tensile mechanical property test that meets national standards. It was found that the yield strength and tensile strength of the aluminum-based composite material were significantly improved, to 316.5MPa and 486.9MPa respectively, the elongation was maintained at 4.6%, and the hardness was also increased to 169.5HV. Figure 2 , 3 It was found that smaller spherical particles were distributed in the matrix, and there were no obvious defects in the structure. The structure parallel to the construction direction was fine equiaxed crystals.
[0037] Example 4
[0038] Step (1) Preparation of composite powder: The selected refractory high entropy alloy powder is TiNbHfZr with a particle size of 15 to 53 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm; weigh a certain mass ratio of refractory high entropy alloy powder and aluminum alloy powder, wherein the mass fraction of TiNbHfZr powder is 2%, and the rest is AlSi10Mg powder, and mix them by ball milling. The sizes of the stainless steel grinding balls used are 1 mm, 3 mm, and 5 mm. Weigh stainless steel balls at a mass ratio of 15:5:3, and the ball-to-material ratio is 1:1. Add the powder and grinding balls into a ball mill and mix for 10 hours, fill with argon as a protective gas, and rotate at 150 rpm. After mixing, sieve through a sieve and dry in a vacuum drying oven at 70°C for 4 hours to obtain a composite powder of TiNbHfZr and AlSi10Mg.
[0039] Step (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling is performed through three-dimensional software and slicing is performed. The composite powder in step (1) is spread flat on the substrate of the SLM metal 3D printer forming cabin. In this embodiment, 5083 aluminum alloy plate is selected, preheated to 180°C, and the protective atmosphere in the printing cabin is argon. The printing process parameters are set as follows: laser power is 340W, scanning spacing is 160μm, powder layer thickness is 30μm, and the scanning speed is graded and regulated: every 5 layers is a cycle, the first layer scanning speed A is 1200mm / s, in this embodiment n=1, and the scanning speeds of the next four layers are 1300mm / s, 1400mm / s, 1500mm / s, and 1600mm / s respectively. Printing of aluminum-based composite materials is carried out in this cycle.
[0040] The prepared aluminum-based composite material was subjected to microstructure characterization, hardness test, and room temperature tensile mechanical property test that meets national standards. It was found that the yield strength and tensile strength of the aluminum-based composite material were significantly improved, to 319.57MPa and 490.68MPa respectively, the elongation was maintained at 4.69%, and the hardness was also increased to 165.3HV. Figure 2 , 3 It was found that there were no obvious defects in the structure, and the structure parallel to the construction direction was fine equiaxed crystals.
[0041] Example 5
[0042] Step (1) Preparation of composite powder: The selected refractory high entropy alloy powder is TiNbZrTaV with a particle size of 15 to 53 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm; a certain mass ratio of refractory high entropy alloy powder and aluminum alloy powder is weighed, wherein the mass fraction of TiNbZrTaV powder is 2% and the rest is AlSi10Mg powder, and mixed in a V-type powder mixer, argon is filled as a protective gas, and the rotation speed is 200 rpm. After mixing, the mixture is sieved through a sieve and dried in a vacuum drying oven at 70°C for 4 hours to obtain a composite powder of TiNbZrTaV and AlSi10Mg.
[0043] Step (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling and slicing are performed using three-dimensional software. The composite powder in step (1) is spread flat on the substrate of the SLM metal 3D printer forming cabin. In this embodiment, 5083 aluminum alloy plate is selected, preheated to 150°C, and the protective atmosphere in the printing cabin is argon. The printing process parameters are set as follows: laser power is 370W, scanning spacing is 140μm, powder layer thickness is 30μm, and the scanning speed is graded and regulated: every 5 layers is a cycle, the first layer scanning speed A is 1100mm / s, in this embodiment n=2, and the scanning speeds of the next four layers are 1300mm / s, 1500mm / s, 1700mm / s, and 1900mm / s respectively. Printing of aluminum-based composite materials is carried out in this cycle.
[0044] The prepared aluminum-based composite material was subjected to microstructure characterization, hardness test, and room temperature tensile mechanical property test that meets national standards. It was found that the yield strength and tensile strength of the aluminum-based composite material were significantly improved, to 323.69MPa and 495.63MPa, respectively, the elongation was maintained at 5.01%, and the hardness was also increased to 169.66HV. Figure 2 , 3 Similar) found that spherical refractory high-entropy alloy particles are distributed in the matrix, and the structure parallel to the building direction becomes equiaxed crystals.
[0045] Example 6
[0046] Step (1) Preparation of composite powder: The selected refractory high entropy alloy powder is TiTaNbZrHf with a particle size of 15 to 53 μm, and the aluminum alloy powder is 2024 series aluminum alloy with a particle size of 15 to 53 μm; weigh a certain mass ratio of refractory high entropy alloy powder and aluminum alloy powder, wherein the mass fraction of TiTaNbZrHf powder is 2%, and the rest is 2024 series aluminum alloy powder, use a V-type powder mixer to mix, fill with argon as a protective gas, the rotation speed is 180 rpm, after mixing, sieve through a sieve and dry in a vacuum drying oven at 70°C for 4h to obtain a composite powder of TiTaNbZrHf and AlSi10Mg.
[0047] Step (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling and slicing are performed using three-dimensional software. The composite powder in step (1) is spread flat on the substrate of the SLM metal 3D printer forming cabin. In this embodiment, a 2024 aluminum alloy plate is selected, which is preheated to 150°C. The protective atmosphere in the printing cabin is argon. The printing process parameters are set as follows: the laser power is 380W, the scanning spacing is 150μm, the powder layer thickness is 30μm, and the scanning speed is graded and regulated: every 5 layers is a cycle, the scanning speed A of the first layer is 1200mm / s, in this embodiment n=2, and the scanning speeds of the last four layers are 1400mm / s, 1600mm / s, 1800mm / s, and 2000mm / s respectively. The aluminum-based composite material is printed in this cycle.
[0048] The prepared aluminum-based composite material was subjected to microstructure characterization, hardness test, and room temperature tensile mechanical property test that meets national standards. It was found that the yield strength and tensile strength of the aluminum-based composite material were significantly improved, to 269.56MPa and 409.38MPa, respectively, the elongation was maintained at 10.26%, and the hardness was also increased to 142.9HV. Figure 2 , 3 Similar) found that spherical refractory high-entropy alloy particles are distributed in the matrix, and the structure parallel to the building direction becomes equiaxed crystals.
[0049] Example 7
[0050] Step (1) Preparation of composite powder: The selected refractory high entropy alloy powder is TiNbZrTa with a particle size of 15 to 53 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 45 to 90 μm; weigh a certain mass ratio of refractory high entropy alloy powder and aluminum alloy powder, wherein the mass fraction of TiNbZrTa powder is 5%, and the rest is AlSi10Mg powder, and mix them by ball milling. The sizes of the stainless steel grinding balls used are 1 mm, 3 mm, and 5 mm. Weigh stainless steel balls at a mass ratio of 15:5:3, and the ball-to-material ratio is 1:1. Add the powder and grinding balls into a ball mill and mix for 10 hours, fill with argon as a protective gas, and rotate at 150 rpm. After mixing, sieve through a sieve and dry in a vacuum drying oven at 70°C for 4 hours to obtain a composite powder of TiNbZrTa and AlSi10Mg.
[0051] Step (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling and slicing are performed using three-dimensional software. The composite powder in step (1) is spread flat on the substrate of the SLM metal 3D printer forming cabin. In this embodiment, 5083 aluminum alloy plate is selected, preheated to 180°C, and the protective atmosphere in the printing cabin is argon. The printing process parameters are set as follows: laser power is 350W, scanning spacing is 150μm, powder layer thickness is 30μm, and the scanning speed is graded and regulated: every 5 layers is a cycle, the first layer scanning speed A is 1400mm / s, in this embodiment n=1, and the scanning speeds of the next four layers are 1500mm / s, 1600mm / s, 1700mm / s, and 1800mm / s respectively. Printing of aluminum-based composite materials is carried out in this cycle.
[0052] The prepared aluminum-based composite material was subjected to microstructure characterization, hardness test, and room temperature tensile mechanical property test that meets national standards. It can be found that the yield strength and tensile strength of the aluminum-based composite material were greatly improved, to 342.6MPa and 522.69MPa respectively, the elongation was maintained at 4.03%, and the hardness was also increased to 183.92HV. Figure 2 , 3 It was found that there were no obvious defects in the structure, and the structure parallel to the construction direction was fine equiaxed crystals.
[0053] Example 8
[0054] Step (1) Preparation of composite powder: The selected refractory high entropy alloy powder is TiNbZrTa with a particle size of 15 to 53 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm; weigh a certain mass ratio of refractory high entropy alloy powder and aluminum alloy powder, wherein the mass fraction of TiNbZrTa powder is 10% and the rest is AlSi10Mg powder, and mix them by ball milling. The sizes of the ZrO2 grinding balls used are 1 mm, 3 mm, and 5 mm. Weigh ZrO2 grinding balls at a mass ratio of 15:5:3, and the ball-to-material ratio is 1:1. Add the powder and grinding balls into a ball mill and mix for 4 hours, fill with argon as a protective gas, and rotate at 150 rpm. After mixing, sieve through a sieve and dry in a vacuum drying oven at 70°C for 4 hours to obtain a composite powder of TiNbZrTa and AlSi10Mg.
[0055] Step (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling and slicing are performed using three-dimensional software. The composite powder in step (1) is spread flat on the substrate of the SLM metal 3D printer forming cabin. In this embodiment, a 5083 aluminum alloy plate is selected, preheated to 150°C, and the protective atmosphere in the printing cabin is argon. The printing process parameters are set as follows: the laser power is 320W, the scanning interval is 150μm, the powder layer thickness is 30μm, and the scanning speed is graded and regulated: every 5 layers is a cycle, the scanning speed A of the first layer is 1000mm / s, in this embodiment n=2, and the scanning speeds of the next four layers are 1200mm / s, 1400mm / s, 1600mm / s, and 1800mm / s respectively. The aluminum-based composite material is printed in this cycle.
[0056] The prepared aluminum-based composite material was subjected to microstructure characterization, hardness test, and room temperature tensile mechanical property test that meets national standards. It was found that the yield strength and tensile strength of the aluminum-based composite material were significantly improved, to 362.59MPa and 550.68MPa, respectively, the elongation was maintained at 3.43%, and the hardness was also increased to 220.69HV. Figure 2 , 3 Similar) found that more spherical particles are distributed in the matrix, and the interface between the refractory high entropy alloy and the aluminum matrix is well bonded.
[0057] Comparative Example:
[0058] In this comparative example, an AlSi10Mg alloy is prepared. Unlike Example 1, no refractory high entropy alloy is added as a reinforcement phase, and the printing process is consistent with that of Example 1.
[0059] Figure 4 The metallographic structure diagram of the comparative example parallel to the construction direction is a typical columnar crystal growing perpendicular to the molten pool direction. The room temperature tensile mechanical properties test results of the comparative example that meet the national standard requirements are as follows Figure 5 The mechanical properties of the refractory high entropy alloy reinforced aluminum-based composites prepared in Examples 1, 2, 3, 4, 5, 7, and 8 are greatly improved compared to the AlSi10Mg alloy, while still having a certain plasticity, indicating that the addition of refractory high entropy alloys and the printing method of graded control of scanning speed can effectively change the growth mode of grains, reduce the anisotropy of the composite material, and thus improve the performance of the composite material.
[0060] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A layered scanning additive manufacturing method for an aluminum-based composite material reinforced with refractory high entropy alloy particles, characterized in that: The following steps are involved: (1) Preparation of composite powder: Weighing refractory high entropy alloy powder and aluminum alloy powder respectively, uniformly mixing them through a powder mixing device, introducing a protective gas, sieving through a standard sieve and drying, to obtain a composite powder of refractory high entropy alloy and aluminum alloy; (2) Layered scanning additive manufacturing of aluminum-based composite materials: Modeling and slicing are performed using three-dimensional software; the composite powder is spread flat on the substrate of the SLM metal 3D printer forming chamber, the substrate is preheated in an atmosphere of protective gas, the laser power and scanning spacing are adjusted, and the scanning speed is graded and controlled: every 5 layers is a cycle, the scanning speed of the first layer is A mm / s, the scanning speed of the second layer is A+n×100mm / s, the scanning speed of the third layer is A+2n×100mm / s, the scanning speed of the fourth layer is A+3n×100mm / s, and the scanning speed of the fifth layer is A+4n×100mm / s. The scanning speed of the first layer of the next cycle is still Amm / s, and so on, so that the laser periodically scans layer by layer on the powder bed to print the aluminum-based composite material.
2. The method according to claim 1, characterized in that The matrix of the refractory high-entropy alloy particle-reinforced aluminum-based composite material is various aluminum alloys, including cast aluminum alloys and partially deformed aluminum alloys; the reinforcing phase is a refractory high-entropy alloy, including TiNbZrTa series, WTaMoNb series, HfNbZrTa series, TiTaNbV series or TiNbHfZr series high-entropy alloys; the cast aluminum alloy is Al-Si series, Al-Cu series, Al-Mg series or Al-Zn series; the partially deformed aluminum alloy is 1 series, 2 series, 4 series, 5 series or 6 series aluminum alloy.
3. The method according to claim 1, characterized in that In step (1), the mass fraction of the refractory high entropy alloy powder is between 1 and 10%, the mass fraction of the aluminum alloy powder is between 90 and 99%, and the sum of the two is equal to 100%; the refractory high entropy alloy powder is spherical and has a particle size between 1 and 53 μm, and the aluminum alloy powder is spherical and has a particle size between 1 and 90 μm.
4. The method according to claim 1, characterized in that: In step (1), the powder mixing equipment is a ball mill or a V-type powder mixer, wherein the ball milling time is 4 to 10 hours, the rotation speed is 120 to 200 rpm, the grinding balls are ZrO2 grinding balls or stainless steel grinding balls, the grinding ball size is 1 to 5 mm, the ball-to-material ratio is 1:1 to 5:1, and the V-type powder mixer mixing time is 4 to 8 hours; after the powders are mixed evenly, they are sieved and dried in a vacuum environment at 70 to 100°C for 3 to 6 hours.
5. The method according to claim 1, characterized in that In step (1), the protective gas is nitrogen or argon.
6. The method according to claim 1, characterized in that In step (2), the substrate used in the printing process is a 1-series, 2-series, 4-series, 5-series or 6-series aluminum alloy, and the substrate is preheated in a nitrogen or argon atmosphere at a temperature of 100°C to 200°C.
7. The method according to claim 1, characterized in that In step (2), the laser power is 300-380 W, the scanning interval is 100-160 μm, and the powder layer thickness is 20-40 μm.
8. The method according to claim 1, characterized in that In step (2), the scanning speed is regulated in stages: wherein n=1, 2 or 3 and n is the same number throughout the entire printing process, and the scanning speeds A mm / s and A+4n×100 mm / s are both in the range of 900 to 2100 mm / s.
9. A refractory high entropy alloy particle reinforced aluminum-based composite material prepared by the method according to any one of claims 1 to 8.
10. The preparation method according to claim 7, characterized in that: The refractory high entropy alloy particles in the composite material are distributed in the aluminum matrix in spherical or a few irregular shapes.
Citation Information
Patent Citations
High-entropy alloy reinforced aluminum matrix composite material and preparation method thereof
CN112191851A
High-entropy alloy and aluminum alloy composite material with high wear resistance and preparation method of high-entropy alloy and aluminum alloy composite material
CN115338410A
Rare earth modified additive manufacturing high-entropy aluminum-based alloy powder, preparation method and application thereof and aluminum-based alloy
CN117107121A
Alloy and member
WO2021193529A1